Boiler performance of emulsified fuel. - Manegdeg, Ferdinand G. (Philippine Engineering Journal)
This research aims to show the performance of using emulsified fuel in a boiler. Bunker and three (3) fuel mixtures consisting of different proportions of bunker, water and catalyst were tested using three (3) nozzle sizes. Samples of the fuels tested including cool were subjected to fuel characteristic tests. A batch mixer was designed and fabricated to blend the fuel mixtures. The fuel mixtures were blended at the experimental sites using the formulated catalyst of the World Energy Extender Corporation. The process of emulsification done and the performance tests conducted are discussed in this study. Fuel characteristic tests were performed based on the codes of the American Society for Testing Materials and the International Organization for Standardization. Boiler performance tests were conducted based on the power test codes of the American Society of Mechanical Engineers. A water tube boiler in conformity with Japanese Industrial Standard code was used. It was observed that the thermal efficiency was lower when firing the boiler with fuel mixtures of bunker, water and catalyst than when only bunker was used. This research only proves that these fuel mixtures can be used as alternative fuels. It is recommended that further study should be conducted to improve and realize the full potential of emulsified fuels.